Toxicidade e atividade antitumoral de um híbrido tiofênico-acridínico - Lisboa, Thais Mangeon Honorato (2020)
Cancer, in the broadest sense, refers to more than 277 different types of carcinogenic diseases that are characterized by disordered growth and metastatic potential. Antitumor effects of thiophenic and acridine compounds are described in the literature, however, the clinical utility of these compounds is limited due to the risk of high toxicity and resistance to treatment. In this context, the molecular hybridization strategy represents an opportunity to develop new drugs that can exhibit better target affinity and reduced undesirable effects. The objective of this work was to evaluate the toxicity and antitumor activity of 2 - ((6- chloro-2-methoxy-acridin-9-yl) amino) -5,6,7,8-tetrahydro-4H-cyclohepta [b] - thiophene-3-carbonitrile (ACS03), a thiophene-acridine hybrid that has antileishmania activity. Toxicity was evaluated in vitro (in non-tumor cell lines - HaCat and L929, and in peripheral blood mononuclear cells - PBMC) and in vivo (zebrafish embryos and acute toxicity in mice). Different human tumor cell lines were used to evaluate antitumor activity in vitro (HCT-116 - colon carcinoma, K562 - chronic myeloid leukemia, HL-60 - promyelocytic leukemia, HeLa - cervical cancer and MCF -7 - breast cancer), while in vivo Ehrlich's ascitic carcinoma model was used, through which toxicity was also assessed after repeated doses (seven days). ACS03 exhibited selectivity in relation to HCT-116 cells (concentration that inhibits 50% of cell growth, IC50 = 23.11 ± 1.03 µM), in addition to having significantly greater activity (p 1,000 µM), however, an increase in the activities of lactate dehydrogenase, glutathione S-transferase and acetylcholinesterase was observed. In the acute toxicity assay, the LD50 value (lethal dose 50%) in mice was estimated at more than 5000 mg / kg (intraperitoneal - ip), and no change in the number of micronucleated erythrocytes was observed in the genotoxicity assay (2000 mg / kg, ip). In vivo, ACS03 (12.5 mg / kg, i.p., seven days of treatment) induced a significant reduction in tumor volume and mass, and in viability and total cell (p <0.05). An increase in nitrite levels (p <0.05) and a reduction in peritumoral vascular microdensity (p <0.05) was observed, associated with a cytotoxic and antiangiogenic effect, respectively. Regarding the main toxicity parameters (biochemical, hematological and histological parameters), evaluated after antitumor treatment, it was observed that ACS03 (12.5 mg / kg) caused only slight changes. In conclusion, the data obtained show antitumor activity in vitro and in vivo for the hybrid ACS03, as well as low toxicity, characterizing it as a potential anticancer compound.